THE NEED TO USE INTERACTIVE TOOLS TEACHING TECHNOLOGIES IIRA FOR CRITICAL FORMATION THINKING OF ECONOMISTS - O.P. Kolesova (Academy of Cognitive and Natural Sciences, 2008)
It is the Article. An author is examine the aspects of forming of critical thought of economists on the basis of component-structural analysis of concept by recomm endations.